Is Customer Retention Beneficial for Customers: A Conceptual Background - Alshurideh, Muhammad Turki (Journal of Research in Marketing (ISSN: 2292-9355), 2016)
Is it healthy for customers to be enrolled in long-term relationships with service organisations? To find a proper answer for such question, this study has been planned. Customer retention is still a dilemma for many organisations these days for a variety of reasons support this idea such as having high competition status, increasing existing customers switching rate and increasing the cost of allocating, classifying and attracting new customers. Thus, a need has been raised to look at different CR issues again from different views such as is CR happening or not supported by providing a proper classification for customer-supplier relationship. Additional themes were discussed such as the relationship strength, longevity, continuity, relational cost and benefits